Radiobiological effects of flattening filter–free photon beams on A549 non-small-cell lung cancer cells. (30th May 2018) - Nakano, Hisashi; Minami, Kazumasa; Yagi, Masashi; Imaizumi, Hiromasa; Otani, Yuki; Inoue, Shinichi; Takashina, Masaaki; Seo, Yuji; Takahashi, Yutaka; Sumida, Iori; Ogawa, Kazuhiko; Koizumi, Masahiko
Abstract: Flattening filter–free (FFF) photon beams minimize the intrafraction motion of tumors, and this feature is useful in pulmonary malignancies, such as non-small-cell lung cancer (NSCLC). However, the radiobiological effects of such beams on NSCLC cells, which are often treated with stereotactic body radiotherapy (SBRT), have not been investigated sufficiently. Although cell motility may be promoted by photon beams with a low dose, the relationship between cell motility and the dose rate of photon beams has not been evaluated. The purpose of this study was to evaluate the radiobiological effects of FFF photon beams on cell survival and motility in NSCLC. A human lung cancer cell line (A549) was irradiated with conventional flattening filter (FF) and FFF photon beams at dose rates of 300 (FF), 500 and 2000 MU/min (FFF). While cell survival was estimated using the colony formation assay, cell motility was evaluated using the Boyden chamber and Matrigel invasion assays. FFF photon beams with a high dose rate neither affected the survival of A549 cells nor caused any significant difference in their motility. On the other hand, high-dose irradiation reduced cell survival and motility regardless of the dose rate. Photon beams with a high dose rate used for radiation therapy are suitable for SBRT from the standpoint of both cell survival and motility, in addition to their physical characteristics.